Shaam-e-Awadh : Writings on Lucknow - Edited by Oldenburg, Veena Talwa (New Delhi Penguin Books, 2007)
Contributed articles on the cultural tapestry of Lucknow city
Keywords: India--Lucknow -- Civilization